Breast Milk: Possible Mechanisms to Shape the Behaviour and Cognitive Functions of a Child - Sergey E. Ukraintsev; Nella S. Paramonova; Irina A. Malyovannaya ("Paediatrician" Publishers LLC, 2018)
The article discusses the possible relationship between breast milk oligosaccharides, the composition of the intestinal microbiota of an infant and his behaviour shaping. The data of research studies performed  both on the model of laboratory  animals and among children, devoted to the study of the effect of intestinal microbiota on shaping behavioural features and cognitive functions is presented.